The Application of Nanotechnological Therapeutic Platforms against Gynecological Cancers - Keyvani, Vahideh; Mollazadeh, Samaneh; Riahi, Espanta; Mahmoudian, Reihaneh Alsadat; Tabari, Masoomeh; Lagzian, Elmira; Ghorbani, Elnaz; Akbarzade, Hamed; Gholami, Amir-Sadra; Gataa, Ibrahim Saeed; Hassanian, Seyed Mahdi; Ferns, Gordon A.; et al. (Current Pharmaceutical Design, 2024)
Gynecological cancers (GCs), ovarian, cervical, and endometrial/uterine cancers, are often associated with poor outcomes. Despite the development of several therapeutic modalities against GCs, the effectiveness of the current therapeutic approaches is limited due to their side effects, low therapeutic index, short half-life, and resistance to therapy. To overcome these limitations, nano delivery-based approaches have been introduced with the potential of targeted delivery, reduced toxicity, controlled release, and improved bioavailability of various cargos. This review summarizes the application of different nanoplatforms, such as lipid-based, metal-based, and polymeric nanoparticles, to improve the chemo/radio treatments of GC. In the following work, the use of nanoformulated agents to fight GCs has been mentioned in various clinical trials. Although nanosystems have their own challenges, the knowledge highlighted in this article could provide deep insight into translations of NPs approaches to overcome GCs.
Keywords: nanoplatforms